Low‐dose interleukin‐2 promotes STAT‐5 phosphorylation, Treg survival and CTLA‐4‐dependent function in autoimmune liver diseases. (20th March 2017) - Jeffery, H. C.; Jeffery, L. E.; Lutz, P.; Corrigan, M.; Webb, G. J.; Hirschfield, G. M.; Adams, D. H.; Oo, Y. H.
Summary: CD4 + CD25 high CD127 low forkhead box protein 3 (FoxP3 + ) regulatory T cells (Treg ) are essential for the maintenance of peripheral tolerance. Impaired Treg function and an imbalance between effector and Tregs contribute to the pathogenesis of autoimmune diseases. We reported recently that the hepatic microenvironment is deficient in interleukin (IL)−2, a cytokine essential for Treg survival and function. Consequently, few liver‐infiltrating Treg demonstrate signal transducer and activator of transcription‐5 (STAT‐5) phosphorylation. To establish the potential of IL‐2 to enhance Treg therapy, we investigated the effects of very low dose Proleukin (VLDP) on the phosphorylation of STAT‐5 and the subsequent survival and function of Treg and T effector cells from the blood and livers of patients with autoimmune liver diseases. VLDP, at less than 5 IU/ml, resulted in selective phosphorylation of STAT‐5 in Treg but not effector T cells or natural killer cells and associated with increased expression of cytotoxic T lymphocyte antigen‐4 (CTLA‐4), FoxP3 and CD25 and the anti‐apoptotic protein Bcl‐2 in Treg with the greatest enhancement of regulatory phenotype in the effector memory Treg population. VLDP also maintained expression of the liver‐homing chemokine receptor CXCR3. VLDP enhanced Treg function in a CTLA‐4‐dependent manner. These findings open new avenues for future VLDP cytokine therapy alone or in combination with clinical grade Treg in autoimmune liver diseases, as VLDP could not only enhance regulatory phenotype and functional property but also the survival of intrahepatic Treg . Abstract : At very low doses of IL‐2, STAT5 phosphorylation is induced selectively in the regulatory T‐cell (Treg) immune subset in patients with autoimmune liver diseases as well as healthy controls, corresponding to high expression of CD25 by Treg. The regulatory phenotypes (CTLA‐4, FOXP3 and CD25 expression) function (CTLA‐4 dependent suppression of responder cell division) and expression of survival factor Bcl‐2 are increased in Treg by low dose IL‐2, without any detectable activation of effector cells. Very low dose IL‐2 might have therapeutic benefit in patients with autoimmune liver diseases.